Peningkatan Hasil Belajar Keterampilan Membaca Melalui Strategi Pembelajaran Card Sort Pada Siswa MTs. Darut Taqwa 02 Sengonagung Purwosari - Rufahniya, Liza; Hasyim, Mochamad (AL MURABBI, 2022)
Learning outcomes in learning reading skill there are 31 students who are still under the KKM. This is because the teacher still uses the lecture method and tadribat only, so that in focused learning with books that can cause students to feel bored and students are still not able to understand the meaning or information contained in the Arabic text. The objectives of this study include; to find out how to use the card sort learning strategy, and to find out how the effect of the card sort learning strategy on improving the learning outcomes of reading skill. This research is a quantitative research type of pre-experiment. The method used is one group pretest-posttest design. The results of this study show that card sort learning strategies have an effect on improving student reading skill learning outcomes. This can be seen from the fact that the calculation is greater than the ttabel, namely 11,614 > 2,030 and Sig. (2 tailed) = 0.000 < 0.05, then Ho was rejected and Ha was accepted. So it can be concluded that there is an influence on the use of card sort learning strategies on improving the learning outcomes of reading skill students of Junior High School Darut Taqwa 02 Sengonagung Purwosari.